Effect of partial replacement of fly ash by metakaolin on strength development of fly ash based geopolymer mortar - Zahid, M. (Trans Tech Publications Ltd, 2017)
This article aims to investigate the compressive strength variation by the addition of metakaolin as a substitute of fly ash in the fly ash based geopolymer mortar. Five, ten and fifteen percent by weight of fly ash was replaced by highly reactive metakaolin. Two type of fly ashes namely, ASTM class F and ASTM class C were used as a base material for the synthesis of geopolymer mortar. Eight molar sodium hydroxide solution mixed with sodium silicate solution was used as alkaline activator. For optimum geopolymerization, mortar was cured at sixty degree Celsius for twenty four hours duration. Results show different behavior of metakaolin replacement on compressive strength for two different types of fly ash based geopolymer mortar. Improvement in compressive strength was seen by addition of metakaolin in ASTM class F fly ash based geopolymer. On the other hand compressive strength was decreased abruptly in fly ash class C based geopolymer up to certain replacement level. © 2017 Trans Tech Publications, Switzerland.